Cinemagraph: effectiveness in delivering content through moving image / Fahmi Samsudin, Sharkawi Che Din and Rosita Mohd Tajuddin - Samsudin, Fahmi; Che Din, Sharkawi; Mohd Tajuddin, Rosita (Faculty of Art and Design, 2022)
Moving elements is a part of interactive approaches that attracts our view to discover more. Different approaches result in a variety of results in delivering information, for example still image is used for poster campaigns and video is used for television commercial ads. Currently, still image and motion image (video) are the major media widely used especially in social media like in Instagram and Facebook. Cinemagraph technique is a new photography technique that combines two media which is video and still image to become a moving image, used to attract viewers at their first impressions. This study is focusing on the introduction of cinemagraph technique to be part of the new approaches especially in social media together with the other two media choices. Purpose of this study is to determine the effectiveness of these three media in delivering the content and see how far viewers react through the content presented. Results from this study are expected to help in gaining data to enhance the next future research, specialized in content study and the technique itself. As for the conclusions, this study only discusses on the surface since the main objective is to introduce the technique and identify the effectiveness of the media.